Cognitive Style, Attitude, and Self Efficacy as Predictors of Student Success in EFL Online Courses at Halu Oleo University - Fithrah Jiwa, Ramdhani Nur; Tanduklangi, Amri; Sailan, Zalili (Halu Oleo University, 2017)
Despite the growing technology, higher education institutions have added online courses to their curriculum and maximize the potential benefits in the classroom. Measuring students’ cognitive style, attitude and self efficacy towards online learning provides a beneficial construct to predict learning outcomes.This study was designed to measure cognitive style, attitude, and self efficacy as predictors of student success in EFL online course at Halu Oleo university. The aim of this study were: (1) examined simultaneous contribution of cognitive style, attitude, and self-efficacy of students’ success in online learning; (2) to examined which variable serves as the better predictor of students’ success in online leaning outcome; and (3) to measure the relationship between students’ cognitive styles, students’ attitude and self-efficacy as predictors of students’ success in online learning outcome. This study adopted a correlation method design. Instruments of the study were questionnaire of Cognitive style inventory; questionnaire of students attitude toward online instruction; and questionnaire of online technology self efficacy scale. The study was conducted at the English Language Education study program, in Halu Oleo University. Subjcet of the study was 120 students who participated in this study by filling out a questionnaire. The result of the study showed that 26.1% of cognitive style’s variance contribution toward online learning outcome. It was about 26.9% of attitude variance contribution toward online learning outcome. It showed about 26.2% of self efficacy’s’ variance contribution toward online learning outcome. Three predictors’ had significantly effect on students’ success in online learning outcome. Further, enter regression analyses revealed a statistically –significant model for cognitive style, attitude and self efficacy as predictors of student’s success in online learning outcome (F =16.524, df=2, R squre = .2999, P < 0.0001) .The findings also showed that attitude was best and strong predictor of students success in students’ online learning outcome. The findings revealed a linear relationship between the three on students’ online learning outcome. There was correlation between three predictors in the strong category.